Numerical writing of people with deafblindness (Práxis Educativa, 2021)
The purpose of this text is to investigate the way in which people with deafblindness write numerically and the relationship between numerical writing and the mathematical thinking of these subjects. We started from the hypothesis that some of the difficulties of these people when learning certain school contents were related to this type of writing, which we assumed was closer to Libras than to the Portuguese language. The methodological approach used was exploratory and descriptive research, of a qualitative nature with field research, with three people with deafblindness. The results point to a numerical writing, already transcoded, more focused on the Portuguese language than on the sign language, differing from what happens with deaf people and approaching the writing of hearing people. We conclude that it is possible to infer about the mathematical thinking of people with deafblindness more influenced by the Portuguese language than by the sign language.Keywords: Special Education. Deafblindness. Numerical Writing.